PENGARUSUTAMAAN GENDER DALAM KEBIJAKAN PENGELOLAAN KERAJINAN TENUN SILUNGKANG DI NAGARI SILUNGKANG KOTA SAWAHLUNTO - Jumiati, Jumiati (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
This study examines the Gender Mainstreaming in Policy Management of Silungkang Weaving Crafts in Nagari Silungkang Sawahlunto. This research was conducted through a qualitative approach. The results of this study indicate that gender mainstreaming in policy management of Silungkang weaving craft in Sawahlunto not well-regulated. However, in the implementation by management of Silungkang weaving craft, Silungkang community have done a long time as the responsibility of all of society, including the involvement of women and men from production to marketing the weaving craft. The implementation of Permendagri Number 15 Year 2008 is also not fully accommodated well by the Sawahlunto Government so there have no regulations found related to gender in Sawahlunto. Key Words: Mainstream, gender, handicraft